Stationary consistent equilibrium coalition structures constitute the recursive core - László Á. Kóczy (Fondazione Eni Enrico Mattei (FEEM), 2009)
We study coalitional games where the proceeds from cooperation depend on the entire coalition structure. The coalition structure core (Kóczy, 2007) is a generalisation of the coalition structure core for such games. We introduce a noncooperative, sequential coalition formation model and show that the set of equilibrium outcomes coincides with the recursive core. In order to extend past results to games that are not totally balanced (understood in this special setting) we introduce subgame-consistency that requires perfectness in relevant subgames only, while subgames that are never reached are ignored.
Keywords: C71; C72; 330; Partition Function; Externalities; Implementation; Recursive Core; Stationary Perfect Equilibrium; Time Consistent Equilibrium